(untitled) (International Journal of Physiotherapy, 2021)
Background: A 15-year-old boy met with a road traffic accident in October 2016. The patient sustained a complete spinal cord injury at T11, resulting in paraplegia. Case Description: Later in 2019, the patient was admitted to our hospital with bilateral recurrent infected pressure sore. The patient underwent extensive wound debridement, antibiotic therapy (intravenous and impregnated beads), acetabular curettage, and resection (Girdlestone procedure) of the left proximal femur followed by gluteus maximus flap grafting to fill the dead space. In addition, the patient received education and counseling, nursing care and nutritional intervention, and comprehensive physical therapy treatment, which includes exercises, ultraviolet-C irradiation, Tension therapy, extracorporeal therapy, education. The patient was discharged in a wheelchair after two months. The follow-up after three months showed the complete healing of pressure sore with improvement in the quality of life. Outcome Measures: Outcome measures were hematological reports, Pediatric Quality of Life, Spinal Injury Association (ASIA) impairment scale, and range of motion by goniometer at the time of admission and discharge. Conclusion: We conclude that pressure sores can be a life-threatening medical complication following spinal cord injury; timely multidisciplinary teamwork is crucial to prevent its reoccurrence.